2018
DOI: 10.1111/trf.14554
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical hemolysis in pediatric patients associated with rapid transfusion and one‐way valve

Abstract: Mechanical hemolysis should be considered when investigating possible hemolytic transfusion reactions, especially with high rates of transfusion and use of a valve. During rapid manual transfusion with the valve, greater resistance was associated with increased hemolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…25 In a study on mechanical hemolysis in pediatric patients, during rapid manual transfusion with the use of a valved device, greater resistance was associated with increased hemolysis. 11 Thus, it can be inferred that the valve could also cause random movements in the fluid and probably a variation in infusion rate, resulting in a higher mean rate and, consequently, increasing Reynolds number. 23 The Reynolds number is used to evaluate the type of flow, whether laminar or turbulent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In a study on mechanical hemolysis in pediatric patients, during rapid manual transfusion with the use of a valved device, greater resistance was associated with increased hemolysis. 11 Thus, it can be inferred that the valve could also cause random movements in the fluid and probably a variation in infusion rate, resulting in a higher mean rate and, consequently, increasing Reynolds number. 23 The Reynolds number is used to evaluate the type of flow, whether laminar or turbulent.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown changes in hemolysis markers attributed to catheter type and size, in addition to infusion rate, infusion equipment used, and the physical properties of PRBCs, such as time in storage. 3,[5][6][7][8][9][10][11][12] Thus, the guiding question of this study was: can the inherent advantages of PICCs with a proximal valve, such as lower rates of occlusion and infection, be extended to the nonoccurrence of significant changes in hemolysis markers? This study hypothesized that the size and gauge of PICCs with proximal valves and the infusion rate influence hemolysis markers of RBC concentrates transfused by the gravity method.…”
mentioning
confidence: 99%
“…This may have important clinical implications for neonates and children because of their smaller body size and rapid increase in haemolysis rate per kilogram of weight. 22 Children's kidneys are more immature, with a lower rate of glomerular filtration, and as a result, they may be predisposed to more complications than those of adults. 23,24 In our study, free haemoglobin levels also significantly increased across the four sampling points, and this may cause deleterious effects in critically ill neonates and children.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study has shown that differences related to the mechanism of delivery may exist, which could reduce the degree of haemolysis. This may have important clinical implications for neonates and children because of their smaller body size and rapid increase in haemolysis rate per kilogram of weight 22 . Children's kidneys are more immature, with a lower rate of glomerular filtration, and as a result, they may be predisposed to more complications than those of adults 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Hospira Plum 360 (ICU Medical), CareFusion Alaris PC model 8015 with pump module 8100 (BD) and Infusomat Space (B.Braun) were directly provided by the manufacturers. Syringe pumps, used for small volume transfusions (<50 mL), 12 were not part of this study.…”
Section: Methodsmentioning
confidence: 99%